Seismic and Sequence Analysis of Middle to Late Miocene Deposits of Northeast Java Basin - Yuniardi, Yuyun (Indonesian Journal on Geoscience, 2015)
DOI:10.17014/ijog.2.2.101-110This study is focused on Middle to Late Miocene sediments. As depicted in the regional geology of Indonesia, the area of study is part of Northeast Java Basin. There are three phases of tectonism in the basin: extensional tectonics at Eocene-Oligocene time, compressional tectonics at Middle Miocene, and compressional tectonics at Miocene-Pliocene time. The result of the study shows three sequences were developing during Middle to Late Miocene, those are: (1) Middle Miocene sequence-1 (MM-1 sequence) consisting of a Lowstand Tract System deposition in Middle Miocene-1 (LST MM-1), Transgressive System Tract deposition in Middle Miocene-1 (TST MM-1), and Highstand System Tract deposition in Middle Miocene-1 (HST MT-2); (2) Middle Miocene sequence-2 (MT-2 sequence), comprising Transgressive System Tract Middle Miocene-1 (TST MM-2), and Highstand System Tract deposition in Middle Miocene-1 (HST MM-2); (3) Late Miocene sequence-1 (LM-1 sequence), composed of a Lowstand Tract System deposition in Late Miocene -1 (LST LM-1) and a Transgressive System Tract deposition in Late Miocene-1 (TST LM-1).